2019
DOI: 10.1186/s12963-019-0188-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of data availability on population health indicators at the regional level across the European Union

Abstract: Background The ability to measure regional health inequalities across Europe and to build adequate population health indices depends significantly on the availability of reliable and comparable data at the regional level. Within the scope of the EU-funded project EURO-HEALTHY, a Population Health Index (PHI) was built. This model aggregates 39 indicators considered relevant by experts and stakeholders to evaluate and monitor population health on the regional level within the European Union (269 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 47 publications
0
37
0
1
Order By: Relevance
“…Moreover, data from the PHI used in this study cover year 2014, and specific data gaps were identified throughout the EU regions and PHI indicators. Constraints on data availability at the regional level were found in dimensions within built environment, lifestyle and health behaviors, and healthcare performance [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, data from the PHI used in this study cover year 2014, and specific data gaps were identified throughout the EU regions and PHI indicators. Constraints on data availability at the regional level were found in dimensions within built environment, lifestyle and health behaviors, and healthcare performance [39].…”
Section: Discussionmentioning
confidence: 99%
“…Indicators were selected through a wide Web-Delphi process where an international panel of 80 stakeholders and experts from multidisciplinary fields shared their views on which factors were deemed relevant to evaluate European population health [38]. The indicator data were collected for the year 2014 and retrieved from different official bodies, such as EUROSTAT, the European Environment Agency (EEA), and the World Health Organization (WHO) [39].…”
Section: The Euro-healthy Population Health Indexmentioning
confidence: 99%
“…Data gaps at the regional level on several indicators led to some adjustments between the conceptual model and the model implemented and available via the WebGIS. Issues with availability and quality of the indicator data at sub-national levels should be fundamentally addressed in order to obtain the full potential of this tool [48].…”
Section: Evidence and Tools Supporting Policy-makers And Stakeholdersmentioning
confidence: 99%
“…Currently, despite significant advances in data harmonisation at the EU level (e.g. Eurostat), there is still room for improved data to monitor and assess specific health determinants [48] that shape health outcomes at different geographical levels in a comparable way [59]. The benefit of using the PHI in the future will be accentuated if there is greater alignment of the data collected from different data sources (in the current PHI not all data were available at the same time and spatial resolution).…”
Section: Further Researchmentioning
confidence: 99%
See 1 more Smart Citation